Akibat Hukum Pembagian Waris Untuk Anak dari Adanya Perkawinan Kedua atau Perkawinan Poligami - El Syavira, Inasa; Yustikarini, Meliyana (Universitas Ekasakti, 2023)
The second marriage or polygamous marriage can be carried out if the conditions have been met and the relevant parties have obtained permission both in the form of an application to the district court in the area where they live and permission from the first wife from a previously existing marriage. This kind of marriage has been carried out by many Indonesian people with a variety of basic reasons and looking for justification so that it can also be carried out. Children or offspring born legally will receive recognition and are clear in the eyes of the law. Heirs who have legitimate children either from their first marriage, second marriage or polygamous marriage have legal position and strength in claiming and receiving their rights to the inheritance of the heirs who have become inherited property. The Civil Code, Marriage Law No. 16 of 2019 and the Compilation of Islamic Law can be a definite description and reference in the calculation and determination of the heirs of the deceased heir. If the determination and distribution are carried out as well, for children or descendants, of course the right to their share will not be wrong and cheated.